Fluorescence In Situ Hybridization (FISH)-Based Karyotyping Reveals Rapid Evolution of Centromeric and Subtelomeric Repeats in Common Bean (Phaseolus vulgaris) and Relatives. Issue 4 (1st April 2016) - Iwata-Otsubo, Aiko; Radke, Brittany; Findley, Seth; Abernathy, Brian; Vallejos, C Eduardo; Jackson, Scott A
Abstract: Fluorescence in situ hybridization (FISH)-based karyotyping is a powerful cytogenetics tool to study chromosome organization, behavior, and chromosome evolution. Here, we developed a FISH-based karyotyping system using a probe mixture comprised of centromeric and subtelomeric satellite repeats, 5S rDNA, and chromosome-specific BAC clones in common bean, which enables one to unambiguously distinguish all 11 chromosome pairs. Furthermore, we applied the karyotyping system to several wild relatives and landraces of common bean from two distinct gene pools, as well as other related Phaseolus species, to investigate repeat evolution in the genus Phaseolus . Comparison of karyotype maps within common bean indicates that chromosomal distribution of the centromeric and subtelomeric satellite repeats is stable, whereas the copy number of the repeats was variable, indicating rapid amplification/reduction of the repeats in specific genomic regions. In Phaseolus species that diverged approximately 2–4 million yr ago, copy numbers of centromeric repeats were largely reduced or diverged, and chromosomal distributions have changed, suggesting rapid evolution of centromeric repeats. We also detected variation in the distribution pattern of subtelomeric repeats in Phaseolus species. The FISH-based karyotyping system revealed that satellite repeats are actively and rapidly evolving, forming genomic features unique to individual common bean accessions and Phaseolus species.